The Handbook of Contemporary Semantic Theory - Lappin, Shalom and Fox, Chris (USA; Wiley Blackwell, 2019)
The book surveys the field from a completely fresh perspective,with a new emphasis on formalisms and methods.Includes the application of modern computational techniques, type theory and probabilistic models.
Author is Emeritus Professor of Computational Linguistics at King's College London, UK.
Includes Bibliographical references
Keywords: Cognitive Science, Artificial intelligence, Semantic Theory